Changes of Soil Moisture from Multiple Sources during 1988–2010 in the Yellow River Basin, China. (24th April 2018) - Lou, Dan; Wang, Guojie; Shan, Chan; Hagan, Daniel Fiifi T.; Ullah, Waheed; Shi, Dawei
Abstract : Soil moisture is a key variable in terrestrial water cycle, playing a key role in the exchange of water and energy in the land-atmosphere interface. The spatiotemporal variations of soil moisture from multiple sources during 1988–2010 are evaluated against in situ observations in the Yellow River basin, China, including the Essential Climate Variable satellite's passive microwave product (S M E C V ), ERA-Interim reanalysis (S M E R A ), the National Centers for Environmental Prediction/Department of Energy's Reanalysis-2 (S M N C E P ), and the Variable Infiltration Capacity model products (S M V I C ). The seasonal soil moisture dynamics of S M E C V and S M V I C appear to be consistent with S M i n s i t u, with significant soil drying in spring and wetting in summer. S M E R A and S M N C E P, however, fail to capture the soil drying before rainy seasons. Remarkably, S M E C V shows large agreement with S M i n s i t u in terms of the interannual variations and the long-term drying trends. S M V I C captures the interannual variations but fails to have the long-term trends in S M i n s i t u . As for S M E R A and S M N C E P, they fail to capture both the interannual variations and the long-term soil drying trends in S M i n s i t u .